Soil compaction and stress propagation after different wheeling intensities on a silt soil in South-East Norway - T. Seehusen; R. Riggert; H. Fleige; R. Horn; H. Riley (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2019)
The objective of this study was to evaluate the effect of wheeling with two different wheel loads (1.7 and 2.8 Mg) and contrasting wheeling intensities (1x and 10x) on the bearing capacity of a Stagnosol derived from silty alluvial deposits. Soil strength was assessed by laboratory measurements of the precompression stress in topsoil (20 cm) and subsoil (40 and 60 cm) samples. Stress propagation, as well as elastic and plastic deformation during wheeling were measured in the field with combined stress state (SST) and displacement transducers (DTS). We also present results from soil physical analyses (bulk density, air capacity, saturated hydraulic conductivity) and barley yields from the first two years after the compaction. Although the wheel loads used were comparatively small, typical for the machinery used in Norway, the results show that both increased wheel load and wheeling intensity had negative effects on soil physical parameters especially in the topsoil but with similar tendencies also in the subsoil. Stress propagation was detected down to 60 cm depth (SST). The first wheeling was most harmful, but all wheelings led to accumulative plastic soil deformation (DTS). Under the workable conditions in this trial, increased wheeling with a small machine was more harmful to soil structure than a single wheeling with a heavier machine. However, the yields in the first two years after the compaction did not show any negative effect of the compaction.